Wheel zone pro centre / Muhammad Fareez Iqwan Mohd Fuad ... [et al.] - Mohd Fuad, Muhammad Fareez Iqwan; Razali, Mohamad Syazwan; Arizu, Izni Munirah; Atan, Nurul Shahirah; Noorzaidrul, Muhammad Syahir; Che Wan Ahmadshaifuddin, Che Wan Ahmad Amzar (2015)
Wheel Zone Pro Centre provides wheel-based sports equipment renting service such as recreation bicycles, fitness bicycles, extreme bicycles and roller blades. Based on our survey, we found out that there a high demand from students to rent wheel-based sports equipment in their campus for fitness, social, and health purpose. Thus, we are here to fulfill the needs of the campus community by transforming demands into great opportunity which is in future will be very profitable business. With all these solid facts and reasons, we all have agreed to open up our wheel-based sports equipment renting service called Wheel Zone Pro Centre.